THE DIFFERENCES OF BILINGUAL AND MONOLINGUAL COMMUNICATION COMPETENCES IN ADOLESCENTS - Rabi’atun Adawiyah; Sholihatul Hamidah Daulay (Universitas Pamulang, 2021)
Communication competence is essential for teenagers’ adaptation and affected by how teenagers used their language in daily communication. This research aimed to identify the difference of communication competency between bilingual teenagers and monolingual teenagers. The type of this research was quantitative with comparative purpose. The population of this research was the young teenagers in Medan. Research’s samples were students of SMAIT Bunayya as monolingual teenagers and students of MA Taruna Qur’an as bilingual teenagers. The number of sample in this research was 20 students; 10 bilingual students and 10 monolingual selected using the method of simple random sampling. The measuring instruments used in the form of communication abilities’ scale was based on the components of communicative competency proposed by Spitzberg and Cupach (in Greene & Burleson, 2003; Payne, 2005), namely knowledge, motivation, and skill. The result of data research using independent sample t-test showed that there was a difference of communication competency between bilingual and monolingual teenagers, especially on knowledge and motivation. As a matter of discussion, this research was conducted in the setting of a still monolingual society.